2017
DOI: 10.15517/ma.v28i2.23561
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de materia seca en un sistema silvopastoril de Tithonia diversifolia en trópico alto

Abstract: The aim of this study was to estimate the intake of dry matter forage (CMSf) by grazing holstein cows. The research was conducted in northern Antioquia highlands; a silvopastoral system with Tithonia diversifolia and Cenchrsus clandestinum (SSP) and a monoculture C. clandestinum were used. Were estimated the CMSf by different methodologies and kikuyu:wild sunflower consumption relation, also the interchangeability of two methodologies was determined. There were two conducted trials, in the first trail SSP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
3
1
9
Order By: Relevance
“…The estimation of the Cayman/L. leucocephala ratio offered to animals was carried out using the agronomic method [16], where the difference between the amount of fodder offered and the amount remaining at the end of each grazing was quantified. On the other hand, the level inclusion of T. diversifolia was estimated by employing the difference between the amounts of fodder offered to animals and the amount remaining at the feeder at the end of each day.…”
Section: Forage Quality Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimation of the Cayman/L. leucocephala ratio offered to animals was carried out using the agronomic method [16], where the difference between the amount of fodder offered and the amount remaining at the end of each grazing was quantified. On the other hand, the level inclusion of T. diversifolia was estimated by employing the difference between the amounts of fodder offered to animals and the amount remaining at the feeder at the end of each day.…”
Section: Forage Quality Parametersmentioning
confidence: 99%
“…In this sense, the total amounts of N excreted per N consumed is low. Therefore, the inclusion of T. diversifolia and L. leucocephala in the diet leads to better dietary N use and, in turn, can improve the use of the low-quality forage and lead to better performance in terms of live weight gain [13,16,60,61]. Additionally, other studies have reported that the exponential increase in N excretion through urine is generated with N intakes above 400 g d −1 [62,63].…”
Section: Dry Matter Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Producción de forraje verde (PFV) y materia seca (PMS) (kg/m 2 ). Para el caso del forraje verde de las pasturas en ambos tratamientos, se hicieron aforos usando la técnica de doble muestreo [17], y en cuanto al SSP, se tuvo en cuenta también el estrato de las arbustivas, al cual se le aplicó la técnica de doble muestreo adaptada [18]. La estimación de forraje verde por m 2 , tanto para las pasturas como para el botón de oro se hizo mediante un análisis de regresión lineal.…”
Section: Variables Evaluadasunclassified
“…respecto a la pastura estuvo influenciada por la oferta de botón de oro. Es decir, que pudo haber sido mayor el consumo de botón oro a una mayor densidad de la arbustiva en el área estudiada, pues en este caso la oferta de MS proveniente del botón de oro fue de 2,53 kg MS por cada 786,86 m 2 , que es baja comparada con un sistema silvopastoril en trópico alto, donde se reportan 3,6 kg de MS por cada 375,9 m 2[18], o con un SSP de alta densidad (4000 arbustos/ha) en trópico bajo, donde se obtuvo un promedio de disponibilidad de biomasa proveniente del botón de oro de un 15%[20].Desarrollo productivo de las novillasEn cuanto al peso y la ganancia de peso (cuadro 5), hubo efecto para el tratamiento, el pastoreo y la interacción tratamiento x pastoreo. El promedio de peso al final del experimento fue de 219,75 ± 28,41 kg para el MONO, y de 217,25 ± 39,81 kg para el SSP.…”
unclassified